# Find the value of y? (2y-1/3)-(y+3/2)=y-2

Question asked by: John2500

Asked on: 16 Sep 2010

(2y-1)/3 - (y+3)/2 = y-2

Xing throughout by 6, we get

6 x (2y-1)/3 - 6 x (y+3)/2 = 6 x (y-2)

2 x (2y-1) - 3 x (y+3) = 6 x (y-2)

4y-2-3y-9 = 6y-12

y-11 = 6y-12

y-6y = -12 + 11

-5y = -1

y = -1/-5 = 1/5

By: appuswathi

Replied at: 19 Sep 2010

Rate Answer

**Comment or provide your answer to this question**

No comments have been added to this question "Find the value of y? (2y-1/3)-(y+3/2)=y-2".

**Ask a New Question**

Find out more about Maths

Maths Questions and Answers

maths school questions Questions and Answers

Next question: maths grade average question

**Become a Member! It's Free >>>**

**Share on Facebook:**
**On Twitter:**
Tweet this!
**Question Keywords**

value **More Questions:**

What Number Is Five Times More Than Nineteen?

What Is £1.76 Increased By 10% To The Nearest Penny

Whats A Modal Group?

How Many Variations?

There Are 12 000 Supporters At A Football Match. 10 000 Are Home
Supporters And The Rest Are Away Supporters. Complete The Ratio Of
Home Supporters To Away Supporters.